A RECORD PRODUCTION FROM AN INTEGRATED FARMING SYSTEM UTILISING SEWAGE ENRICHED WATER - RAI, S. P.; ROY, A. K.; DATTA, A. K.; Das, C. R.; GHOSH, J. K. (Journal of Indian Fisheries Association, 2015)
The results of experiments conducted on a pond dyke (655m2) in the Wastewater Aquaculture Division of the Central Institute of Freshwater Aquaculture, Rahara, during 1992-93 for maximising production through optimum utilisation of resources are communicated. Round the year intensive cultivation of okra (Abelmoschus esculentus), amaranth (Amaranthus gangeticus and A. viridus), water-bind weed (Ipomea aquatica), Indian spinach (Basella rubra), radish (Rap han us sativum), amaranth (Amaranthus viridis), cauliflower (Brassica oleracia var. votrytis), cabbage (Brassica oleracia var. capitata) and papaya (Carica papaya) was undertaken using the treated sewage water from fish ponds for irrigation. The pond dyke yielded 5,626.5 kg vegetable which worked out to 85.9 tons per ha per year. Multiple cropping with these vegetables excluding papaya on a 460 m2 dyke recorded a production of 4,926.5 kg at tlle rate of 107.lt per ha/yr. An improved yearly net return of about 35% over investment could be achieved through the selection of highly productive and pest resistant vegetable crops of longer duration for integration into the system. Introduction of this type of integrated farming would enhance the overall productivity and returns from farming.